PERAN MUHAMMADIYAH DALAM PENGUATAN MODAL SOSIAL TERKAIT HUBUNGAN ANTAR KOMUNITAS MUSLIM DI ASEAN - Anam, Rifqi Khairul (LPPM STAI Muhammadiyah Probolinggo, 2023)
Consolidation of Muslim communities in Southeast Asia is still far expectations due to the degradation of a sense of belonging among the Muslim community in any Asian countries, can be seen from the persecution of Muslims in several Asian countries. Therefore, this paper will discuss the role of Muhammadiyah to strengthening of sosial capital as a concrete step consolidation of Muslim communities in Southeast Asia. Sosial capital becomes an important factor in strengthening international Muslim community because in it the inherent trust, networks, and norms in which sosial capital can provide access to a wider network of information so that the consolidation of Muslim communities in Southeast Asia who do do to eliminate Muslim discrimination in several southeast Asian countries.Keywords:Muhammdiyah; Social Capital; Muslim Community